2011
DOI: 10.32607/20758251-2011-3-1-77-84
|View full text |Cite
|
Sign up to set email alerts
|

A In Vitro and In Vivo Study of the Ability of NOD1 Ligands to Activate the Transcriptional Factor NF-kB

Abstract: Pattern-recognition receptors (PRR) play a crucial role in the induction of the defense reactions of the immune system against pathogenic bacterial and viral infections. The activation of PRR by specific, highly conserved pathogen-associated molecular patterns (PAMPs) induces numerous immune reactions related both to innate and adaptive immunity. In addition to the well-studied Toll-like receptors, pathogens can be recognized by the receptors belonging to the other PRR families; including NOD-like receptors (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…Conversely, the role of NLRs in the regulation of inflammation and angiogenesis is not yet fully understood. Some members of the NLR family, including NOD1 and NOD2 were reported to activate NF-κB [168,169], while other members, including NLRP2 [170], NLRP6 [171,172], NLRP12 [173,174], NLRC3 [173] and NLRX1 [175] were reported to negatively regulate NF-κB signaling. However, the inhibitory functions of these NLRs are not well understood [176].…”
Section: Nlrs In Diabetic Retinopathymentioning
confidence: 99%
“…Conversely, the role of NLRs in the regulation of inflammation and angiogenesis is not yet fully understood. Some members of the NLR family, including NOD1 and NOD2 were reported to activate NF-κB [168,169], while other members, including NLRP2 [170], NLRP6 [171,172], NLRP12 [173,174], NLRC3 [173] and NLRX1 [175] were reported to negatively regulate NF-κB signaling. However, the inhibitory functions of these NLRs are not well understood [176].…”
Section: Nlrs In Diabetic Retinopathymentioning
confidence: 99%
“…Diaminopimelic acid is also the active constituent of other environmental PAMPs. For example, dipeptide γ‐D‐glutamyl‐meso‐diaminopimelic acid (iE‐DAP, MW: 319·3), L‐alanyl‐γ‐D‐glutamyl‐meso‐diaminopimelic acid (MW: 390·39) and lauroyl‐γ‐D‐glutamyl‐meso‐diaminopimelic acid (MW: 501·61) are components of peptidoglycan in the cell walls of Gram‐negative and certain groups of Gram‐positive bacteria .…”
Section: Kd Aetiologymentioning
confidence: 99%
“… 12 NOD1 is highly expressed in inflammatory cells, which can active multiple inflammation associated with signaling pathways and result in inflammatory cytokine secretion. 19 , 20 In this study, we investigated the regulatory role of NOD1 in COPD, and found that the expression level of NOD1 was significantly increased in the lung tissues of COPD mice. Similar to COPD treatment, NOD1 activation could facilitate inflammatory responses and increase the number of macrophages, neutrophils and lymphocytes in BALF of mice.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] NOD1 is highly expressed in inflammatory cells, which activates the NF-κB signaling and results in the secretion of inflammatory cytokines. [19][20][21] Recent studies have reported that NOD1 activation could cause tissue inflammation in the heart and aggravate cardiac ischemia-reperfusion injury. 16,22 NOD1 is widely expressed in lung tissues.…”
Section: Introductionmentioning
confidence: 99%